Transformational Leadership in Increasing the Quality of Educational Human Resources - Amet Amet; Deni Kurnia (STAI Miftahul Ula Nganjuk, 2023)
Islamic educational institutions must devise effective strategies in the current era of information openness and transformation, keep up with changes in people's lives, offer the best level of community service, and produce breakthroughs, innovation, and limitless creativity in order to be recognized and gain the public's trust as institutions capable of managing education. The data gathering methods used in this study are interviews and documentation, utilizing a descriptive qualitative model approach. Techniques for data analysis used a qualitative descriptive model approach This study discovered that, although though SDIT is typically found in metropolitan regions, Ash Sholihat may persuade the community to support the development of schools in rural areas by using the transformational leadership model at SDIT.